SINH KHOÁNG PERMI - TRIAS MIỀN BẮC VIỆT NAM - Hòa, Trần Trọng; Anh, Trần Tuấn; Dung, Phạm Thị; Phượng, Ngô Thị; A.S, BORISENKO; A.E, IZOKH (Vietnam Journal of Earth Sciences, 2011)
Permo-Triassic metalogeny of North Vietnam The Permo-Triassic period in North Vietnam has determined three ore complexes, formed in the different structures: 1/ Cu-Ni-(PGE) and Ti-Fe-V ore complex; 2/ gold-sulfide and 3/ tin-sulfide. The first complex consists of Cu-Ni-(PGE) mineralization associated with differentiated mafic-ultramafic intrusions of various volcano-plutonic types of the Song Da, Song Hien rift zones, and fold belts surrounding the Song Chay Dome. The Cu-Ni-PGE and Ti-Fe-V complexes, temporally corresponding to the two stages of plume magmatic activities: 260 Ma (Song Hien and Song Da) and 250 Ma (Phu Ngu-Lo Gam), similar to the associated ore occurrences of Emeishan LIP in Southwest of China (Limahe, Jang Baoshan, Panzhihua,...). Gold-sulfide ore complexes, including Au-As, Au-Sb, Sb-Hg-Au and Hg-Sb-(Au) types widespread in the Song Da and Song Hien rift zones as well as in Paleozoic Lo Gam and Quang Ninh folded structures. Within these structures, ore distribution in the form of ore nodes: Lang Vai, Lang Neo, Loc Shoa, Khe Chim ... Common features of these ore nodes are similar ore chemistry(Au, Sb, As, Hg) and zonation: Au-As → Au-Sb → As-Sb-Hg → Hg, as well transitional relations between different types of ore: Au-As and Au-Sb, Au-Sb and Sb-Hg (Lang Vai, Lang Neo ore nodes,...). Ages of ore formation of this complex range from 252-229 Ma, and spatial correlation with bimodal volcano - plutonic (basalt - rhyolite, rhyolite - basalt, granite - porphyry) as well as with small granite and gabbro - syenite intrusion, with age variation of about 247 -233 Ma.